Pengaruh Disiplin Ilmu Terhadap Kecenderungan Mahasiswa Dalam Mengakses Informasi Melalui Media Sosial Menggunakan Metode Chi Square - Retno Palupi; SM Santi Winarsih (STMIK Sinar Nusantara, 2021)
Social media becomes necessity that is always consumed by many levels of society to looking for such of information. Social media services provide many features that make users can enjoying seaching in cyberspace. All the level of society, all the level of social background and all the level of professions are very familiar with various social media. Social media services on gadgets have facilities to obtain information quickly and easily, such as Facebook, Instagram, YouTube and etc. This study examines the usage of smartphones to determine whether there is a significant effect of students from various disciplines on the tendency of students to access the information needed to support assignments or to find out the required data through social media. The Chi Square method is used as a testing method to determine the effect of disciplines on student tendencies in accessing information topics through social media. The data analysis gave the measurable results based on quantitative data and interesting information. The results showed that the influence of the field of study on students’ Tendencies depend on intensity time in accessing social media.